Coaches' role in youth sports performance: early specialization versus long-term development - Morais, J. E.; Marinho, D. A.; Castro, F. A. D. S.; Barbosa, T. M. (Frontiers in Psychology, 2021)
Youth sports are planned sports programs for children and adolescents with designated coaches, organized practices, and scheduled competitions. Such programs can be organized and implemented at schools (by physical education teachers instead of coaches), as well as in other sports organizations (i.e., federations, associations, local clubs). Primary aim should be to focus on providing young athletes with fundamental motor skills in tandem to their maturation stage. Indeed, these programs are aimed at mass participation rather than on developing elite athletes. The participation in such programs during childhood and adolescence showed to have major benefits in children's and adolescent's physical, psychological, and social development. On the other hand, youth sports programs can also serve as a link to talent identification and development programs aiming to identify young athletes with potential for success in adult/elite sport. As they are mass orientated, many youth athletes can be observed which will increase the likelihood of talent identification. Afterwards, these athletes can be guided to high-performance programs aiming to achieve eventually an elite level.